2015
DOI: 10.1186/s12978-015-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early resumption of sexual intercourse among postnatal women in Uganda

Abstract: BackgroundDespite being a key component to be addressed during postnatal period, sexuality has long been a subject of secrecy and taboo in Africa. Resumption of sexual intercourse after giving birth has been shown to reduce extramarital affairs and consequently reduce risk of sexually transmitted infections like HIV/AIDS. Consequences of early resumption of sexual intercourse include unwanted pregnancy, genital trauma and puerperal infection. The objective of the study was to assess prevalence and factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
57
6
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 16 publications
17
57
6
3
Order By: Relevance
“…Infected individuals are considered to be incapable of functioning normally, and in severe cases, they are forced to withdraw from occupational responsibilities. To a significant extent, they are perceived as threats, they face long-term, damaging degradation of their life style and, additionally, they have to cope with the everlasting stigma 2730…”
Section: Transmission and Discrimination In Modern Societiesmentioning
confidence: 99%
“…Infected individuals are considered to be incapable of functioning normally, and in severe cases, they are forced to withdraw from occupational responsibilities. To a significant extent, they are perceived as threats, they face long-term, damaging degradation of their life style and, additionally, they have to cope with the everlasting stigma 2730…”
Section: Transmission and Discrimination In Modern Societiesmentioning
confidence: 99%
“…6 Studies in Uganda show that 22—58% of women resume sexual activity by 6 weeks after birth. 8-10 The median time to contraceptive use among postpartum women in Uganda is estimated to be 19 months after resumption of sexual intercourse. 11 …”
mentioning
confidence: 99%
“…This may also explain the persistently high fertility observed in Malawi . Studies from Uganda and Kenya also reported that early resumption of sexual activity after delivery and fertility desires were associated with social, demographic, and societal factors …”
Section: Discussionmentioning
confidence: 99%